Performance and metabolic responses of highly-trained team-sport athletes during repeated sprinting in hypoxia - Morrison, J. D.; Lovell, D.; McLellan, C.; Minahan, C. (Journal of Athletic Enhancement, 2015)
To examine the performance (i.e., peak and mean speed) and metabolic responses (i.e., O2 uptake and blood lactate concentration) of highly-trained team-sport athletes during repeated sprinting in hypoxia. Seven professional Australian-rules football players (i.e., AFL players; age, 20 ± 1 yr; stature, 190 ± 6 cm; body mass, 86.4 ± 9.8 kg) participated in this study. AFL players were required to complete ten, 6-s sprints with 24 s recovery (i.e., repeated-sprint running test; RSR test) on a non-motorised treadmill in normobaric normoxia, FiO2: 20.9% (RSN) and in normobaric hypoxia, FiO2: 14.0% (RSH). Peak and mean speed were determined, and oxygen uptake, blood lactate concentration and arterial oxygen saturation were obtained to examine metabolism.